KLRG1 expression identifies short-lived Foxp3+ Treg effector cells with functional plasticity in islets of NOD mice. (18th August 2017) - Kornete, Mara; Mason, Edward; Istomine, Roman; Piccirillo, Ciriaco A.
Abstract: A progressive waning in Foxp3 + regulatory T (Treg ) cell function provokes autoimmunity in the non-obese diabetic (NOD) mouse model of type 1 diabetes (T1D), a cellular defect rescued by prophylactic IL-2 therapy. We showed that most islet-infiltrating Treg cells express inducible T-cell co-stimulator (ICOS) in pre-diabetic NOD mice, and that ICOS + Treg cells display enhanced fitness and suppressive function in situ . Moreover, T1D progression is associated with decreased expansion and suppressive activity of ICOS + Foxp3 + Treg cells, in islets, an observation consistent with the exacerbated T1D seen in NOD.BDC2.5 mice in which the ICOS pathway is abrogated. Here, we show that a large proportion of islet-resident Treg cells express the KLRG1 marker of terminally differentiation, in contrast to islet-infiltrating ICOS − Treg or Teff cells. We hypothesized that KLRG1 expression designates a subpopulation of ICOS + Treg cells in islets that progressively loses function, and contributes to the immune dysregulation observed at T1D onset. Indeed, KLRG1-expressing ICOS + Treg cells are prone to apoptosis, and have an impaired proliferative capacity and suppressive function in vitro and in vivo . T1D protective low-dose IL-2 treatment in vivo could not rescue the loss of KLRG1-expressing Treg cells in situ. While the global pool of Foxp3 + Treg cells displays some degree of functional plasticity in vivo, the KLRG1 + ICOS + Treg cell subset is particularly susceptible to lose Foxp3 expression and reprogram into Th1- or Th17-like effector T (Teff ) cells in the pancreas microenvironment. Overall, KLRG1 expression delineates a subpopulation of dysfunctional Treg cells during T1D progression in autoantigen-specific TCR transgenic NOD mice.